Safety practices of scaffolding at construction site / Malazubida Mansor - Mansor, Malazubida (Faculty of Architecture, Planning and Surveying, 2013)
Scaffoldings act as an important part of the temporary structure during the building construction by providing platforms for allowing the workers to carry out their work at high place. Literatures reveal the importance of safety performance and cost effectiveness as well as their close relationship in construction. The objectives are to identify the hazards in scaffolding work at construction sites, to evaluate the safety performances of scaffolding, to evaluate the cost effectiveness of scaffolding and to identify good practices in scaffolding work. To achieve this goal, survey was carried out based on various literature as well as questionnaires. The method of site survey employ Likert Scale among project manager, safety officer, site safety supervisor, engineer, quantity surveyor and others in 25 construction sites at Selangor. The data collected was analyzed using the average index formula. The result of study shows that the contractors implemented good safety performances and cost effectiveness of scaffolding at construction sites in compliance with regulations and requirement set by OSHA and FMA.